Downstream market structure and the incentive for innovation in telecommunication infrastructure - Nina Czernich (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2008)
This paper addresses the question of how the competitive situation in the downstream market, the services, and the innovative activity in the upstream market, the network infrastructure, interact. The focus is on the vertical structure of the telecommunication market, which is analysed in the framework of a patent licensing model. The paper considers an integrated network provider who can implement a new technology for the network which reduces the costs of offering services over the network. This provider can charge a mark-up above the new lower cost level from the service providers for the use of the new technology. The level of the mark-up is determined by a regulator who aims at promoting innovation. It can be shown that the network providers incentive to innovate increases with the number of competitors, given that the mark-up is sufficiently high. Hence, there exists a range for the mark-up where increasing competition in the service market and more innovative investment in the network infrastructure can be achieved simultaneously.
Keywords: L24; L42; L51; L96; O31; 330; Telecommunication; innovation; vertical structure; licensing; regulation